Functional and radiological outcome of unstable thoracolumbar burst fracture : operative versus conservative treatment - Hassan, Nadiah Nik (2018)
Introduction Definitive treatment of unstable thoracolumbar fractures has become controversial in spinal surgery practice. The purpose of this study was to evaluate the short term functional and radiological outcome of unstable thoracolumbar burst fractures treated conservatively and operatively. Materials and Method From January 2011 to December 2015, 529 patients with thoracic and lumbar fractures was admitted to our institution. Only 39 patients completed 6 months follow up with complete medical records and radiographs images. Twenty-two (22) single-level unstable thoracolumbar fractures treated conservatively with thoracolumbar orthosis or body cast with early ambulation for 12 weeks and 17 patients treated operatively with posteriorinstrumentation and decompression. Retrospectively, we have included the patient who were proposed for operative treatment for spinal instability and neurological deficit but opted for conservative treatment. The ASIA grading, Denis Pain Scale and Denis Work Scale were used to assess the functional outcome and kyphotic angle, anterior vertebral body height were used to assess the radiographic outcome after six months follow up. Statistical analysis done using SPSS ver. 23 and STATA ver.14 Results Nineteen out of twenty-two patients in conservative group and nine out of seventeen patients in operative group and had intact neurological status. One patient had deterioration of neurological status in conservative group but none in the operative group developed the same complication. In conservative group, one patient (4.5%) and four patients (23.5%) from operative group had improvement of ASIA grading. There were significant differences in kyphotic angle and anterior column height between both groups. However, both groups showed no significant difference of pain status according to Denis Pain Scale with four (18.1%) patients from conservative group and three (17.6%) patients from operative group had no pain while the rest of the patients had mild pain with none of them experienced severe pain and disability. According to Denis Work Scale, 11 (50%) patients from conservative group and 4 (23.5%) patients from operative group returned to previous employment. Two patients from each group were unable to return to full time work. There was no significance difference in between two groups in term of Work Status. Conclusion Conservative treatment is an acceptable alternative method to treat unstable thoracolumbar fractures without neurological deficit for those who are not keen for surgical intervention. Operative stabilization in combination with decompression offer opportunity for neurological recovery.